Population dynamics of the cashew leafminer, Eteoryctis gemoniella (Lepidoptera: Gracillariidae), and inventory of its parasitoids in cashew orchards of Northern Benin, West Africa. (17th January 2018) - Agboton, Cyriaque; Onzo, Alexis; Akohou, Hermine A.; Goergen, Georg; Vidal, Stefan; Tamò, Manuele
Abstract: In this study, we investigate the spatio-temporal fluctuations of the cashew leafminer Eteoryctis gemoniella Stainton, which was recently reported as one of the most devastating cashew pests in Benin. Eteoryctis gemoniella causes serious damage, especially to the young tender leaves, thus reducing the photosynthetic capacity of trees and hence their productivity. This study was carried out in three different cashew orchards in Northern Benin, West Africa, where we monitored the fluctuations of the infestation rates and population changes of E. gemoniella during a one-year cycle, from September 2010 to August 2011. In addition, we collected cashew leaves with mines to check for emergence of hymenopteran parasitoids. Our results show that infestation rates (as well as population densities of E. gemoniella ) varied through time and among orchards. The most infested orchard was at Korou, whereas, the least infested was at Okoutaossé. In general, infestation rates and number of mines per leaf passed through two peaks, the first in July–August and the second in November, whereas no infestations were observed from January to June. Spatial distribution pattern of E. gemoniella within the orchards showed that this moth almost has a random distribution. Parasitoids attacking the leafminer were recovered from the samples. These were Apanteles sp., Chelonus (Microchelonus) nr. curvimaculatus Cameron (Hymenoptera: Braconidae) and Trathala sp. (Hymenoptera: Ichneumonidae). Further detailed studies on these natural enemies will be needed for evaluating their potential in controlling E. gemoniella in cashew orchards.